Tropical Tannin for Engineering Application - Nor Adzwa Binti Rosli; Wan Asma Ibrahim; Zulkafli Hassan; Azizul Helmi Bin Sofian (Universitas Gadjah Mada, 2020)
In this study, some approaches have been proposed to establish an alternative and option of brand-new compounds by using green sources that can minimize the environmental threat in the engineering application industry. Tannin, a chemical component extracted from plant origin, has the potential to bind with proteins and other polymers. The description of tannin can be amplified to cover a complete mass of constituents which give typical phenolic reactions, and hence, it has the properties to interact with the aqueous solution. The potential of tannin to associate allows its usability in the oil and gas industry. The aim of this review in this particular context will be emphasized the use of tannin in the implementation of drilling fluid, mercury removal, wastewater treatment, and corrosion inhibitor.